Yorùbá photoplay magazine as a three-modal arts – the atọ́ka example (2018)
Photoplay magazine was a veritable media of dramatic production for Yoruba theatre practitioners in South-West Nigeria between 1967 and 1991. It was a secondary media of production as the plays published in photoplay magazines were first usually produced on stage, which is the primary home and the homing ground of drama. Atoka was the first and the prime of all photoplay magazines that existed in Yoruba. This paper focuses on the principal arts of photoplay which are dramatic arts, photographic arts and publishing arts. Employing the theory of New Historicism, this study traces the evolution of Atoka photoplay magazine; identifies the three- modal arts of Atoka; examines the concept, constituents and interrelationship of these arts and their impact on the overall success of the magazine as a publication.